ANALISIS KESALAHAN SISWA PADA PERBANDINGAN TRIGONOMETRI BERDASARKAN TEORI NEWMAN - Kristiani Kristiani; Gianti Anjarwati; M Khafid Irsyadi; Sitta Khoirin Nisa (INSPIRAMATIKA, 2023)
The purpose of this study was to determine the types of student errors in trigonometry material based on Newman's theory and the causes of these errors. This study uses a qualitative approach and descriptive research type. Research instruments in the form of tests, interviews, and documentation. In this study, 3 subjects with different abilities were taken, namely students with high abilities, students with moderate abilities and students with low abilities. Based on the results of the study, it was concluded that: the most frequent types of errors made by the first students were comprehension errors or errors in understanding information. Second, process skill errors or calculation process skill errors. Third, the transformation error or error determines the formula where students are wrong in writing the formula to be used. Fourth, encoding errors. The causative factor is that students do not understand the concept of trigonometry material and do not master the concept so that students are unable to relate it to the previous material. Students do not know the problem-solving techniques, are not careful in working and are in a hurry or cannot take advantage of the time allotted.